About the equivalent replaceability of the double induction axiom - Maliaukienė, Livija (Lietuvos matematikos rinkinys, 2009)
In this paper the first order predicate calculus with the axioms of additive arithmetic is investigated. The conditions of the equivalent replaceability of a double induction axiom is presented.